Irradiation Effects on Microstructure and Dielectric Properties of Ba[(Mg0.32Co0.02)Nb0.66]O3 [BMCN] Thin Films - N.V. Patel; Bhagwati Bishnoi; P.K. Mehta; Ravi Kumar; R.J. Choudhary; D.M. Phase; V. Ganesan; C.J. Panchal (Журнал нано- та електронної фізики)
Ba[(Mg0.32Co0.02)Nb0.66]O3 [BMCN] thin films prepared on Pt-Si, MgO, Silicon and ITO coated glass substrates by Pulsed Laser Deposition Technique are investigated. Relative growth parameters suggest that ITO coated glass substrate has good potential for growing films with near Nano size columnar grains. In comparison to bulk, dielectric constant and dielectric loss increases in BMCN films. This undesirable rise in dielectric loss can be drastically reduced by a factor of more than 1/100th times through Ag15+ ion irradiation at 1 × 1012 ions/cm2 dose.